An In-Depth Analysis of the Contribution of the Human Development Index and Labor Force to the Gross Regional Domestic Product in Regencies/Cities of Jambi Province - Azizah Al Munawaroh; Viola Novaryca; Anggun Putri Amelia; Eliyana; Amelia Yustria (www.amertainstitute.com, 2025)
This research is entitled